Perception About the Use of Over-the-Counter Antibiotics Among Patients Attending Outpatient Department of a Tertiary Care Hospital of Bangladesh - Ahmed, Md Ashraf Uddin; Morshed, ASM; Yasmin, Farzana; Chakraborty, Dwijraz (Ibrahim Cardiac Medical Journal, 2020)
Background & objective: Antibiotics are considered among the most commonly sold drug classes in the developing countries. The irrational and overuse of antibiotics result not only in the emergence of resistant bacterial strains but also adverse reactions and economic burden on national health system. This study was carried out with the focus to assess the awareness, attitude and practice of patients visiting Outpatient Department (OPD) of Bangladesh Institute of Research & Development in Endocrine & Metabolism (BIRDEM) General Hospital. towards antibiotic usage and development of its resistance Methods: This cross-sectional study was done in the OPD of BIRDEM General Hospital from June 2017 to July 2017. Patients presented at OPD were selected by convenient sampling. The total number of respondents was 100. A semi-structured questionnaire was used to collect information from the respondents. Data were analyzed using statistical package for social sciences (SPSS) version 20.0 and descriptive statistics were used to analyze the data. Results: Of all the participants who took part in the study, 46% had no knowledge and 36% were unaware of ill-effects of antibiotic resistance. Over half (54%) of the patients showed confusion between antibiotic and antiviral drugs. Investigating patients’ practice about antibiotics revealed that 50% patients used to take incomplete antibiotic course and 30% patients shared their antibiotics with other sick family members. During emergencies, 16% patients used the previously left-over antibiotics without seeing the expiry date. Nearly half (46%) of the patients had a practice of taking previously prescribed antibiotic again for the similar nature of illness without consulting a doctor, 6% patients sought antibiotics prescription whenever they consult a doctor. Conclusion: Although the results of this study cannot be generalized to all adult Bangladeshi, indiscriminate use of antibiotic and unawareness of antibiotic resistance and poor attitude towards the antibiotic usage can be a concern for antibiotic resistance in Bangladesh. It highlights the need of educational interventions to increase awareness of people about the consequences of antibiotic misuse and also to develop healthy attitude to practice antibiotic usage. Ibrahim Card Med J 2019; 9 (1&2): 42-48